Reimagination of English Language Learning for Vocational Education: An Industry 5.0 Oriented English for Specific Purposes Learning Framework - Budi Indra Syahdewa (Solo Universal Journal of Islamic Education and Multiculturalism, 2026)
Objective: To analyze the development of English for Specific Purposes (ESP) learning in vocational education and propose an Industry 5.0-oriented learning framework. Theoretical framework: The study integrates ESP, Industry 5.0, employability skills, digital learning, and constructivist learning theories. Literature review: Previous studies emphasize ESP and digital learning, but a comprehensive framework integrating AI, Industry 5.0, and employability skills in vocational education remains limited. Methods: A qualitative Systematic Literature Review (SLR) was conducted by synthesizing articles from reputable databases using content and thematic analysis. Results: The findings indicate that effective ESP learning requires the integration of industry needs analysis, adaptive curriculum design, AI-supported learning, digital learning ecosystems, project-based learning, and employability skills, including communication, collaboration, critical thinking, creativity, and adaptability. These components form the basis of an integrated conceptual learning framework. Implications: The proposed framework provides practical guidance for vocational institutions, educators, and curriculum developers in designing adaptive, technology-enhanced, and industry-aligned English learning to strengthen graduate competitiveness in the Industry 5.0 era. Novelty: This study proposes an integrated Industry 5.0-Oriented ESP Learning Framework that combines AI, digital learning, industry needs, and employability skills into a single conceptual model for vocational English education.